AI-assisted beach management: Leveraging geoportals for insights from M'diq collectivity - Lahlouh Ayoub; Ben Driss Nisserine (E3S Web of Conferences)
Effective beach management is vital for coastal sustainability. In M'diq, Morocco, a GIS-based geoportal has improved management with tools like interactive maps and real-time data. This study integrates an AI chatbot, leveraging OpenAI API, to enhance user interaction and data accessibility. The chatbot enables natural language queries, generates charts, provides safety tips, and shares data on nine beaches. Preliminary testing shows it simplifies GIS data for non-experts, supporting informed decision- making and sustainable management. Despite limited data, the chatbot shows promise for scalability and broader application. Future work will refine its features and expand testing.